An Error Analysis in Using Passive Voice at Twelfth Grade Students of SMAN 5 Bukittinggi - Firdaus, Muhammad Ryan; Safitri, Loli; Irwandi, Irwandi; Eliza, Eliza (Continuous Education: Journal of Science and Research, 2024)
This research aims to explain the analysis of errors in using passive sentences in class XII students of SMAN 5 Bukittinggi. To explain these errors, the researcher used Bluman's formula to see the percentage of errors made by students, and also the researcher categorized them based on the types of errors made by students. The location of this research was class XII IPS 3 SMAN 5 Bukittinggi with a sample of 33 students. Based on the text, the total percentage of errors for each tense from highest to lowest with a total average, namely from Past Progressive Tense with an average of 38 errors from 3 questions or 23.9% errors. Next, Simple Future Tense with an average of 28 errors out of 3 questions or 17.6% errors. Next, Simple Past Tense with an average of 19 errors out of 4 questions or 15.9% errors. Next, Present Perfect Tense with an average of 24.7 errors out of 3 questions or 15.5% errors. Next, Present Progressive Tense with an average of 17 errors out of 4 questions or 14.3% errors. The lowest is Simple Present Tense with an average of 20.3 errors out of 3 questions or 12.8% errors.